Daur Ulang KKG Bekas - Triyanto Hadisoemarto (Jurnal Kimia dan Kemasan, 2000)
Old Corrugated Container (OCC) is generally corrugated carton material and can range in cleanliness from boxplant clippings to post consumer or grocery store waste. OCC fa· recycled and used in addition to virgin wood fiber in manufacturing a number of g; ades of paper, especially linerboard and corrugating medium. The converting process poses a recycling problem because of the stickies contaminants associated with these operations,nevertheless the size can be reduced by wet end chemical additives. Meanwhile, a new process for upgrading of recycled fibers involves the use of oxygen delignification which gives the fiber a more 'virgin like' character through the softening and better swelling properties that result from lignin removal, has been introduced.